Le progrès, le transfert et le choix technologiques dans les pays en voie de développement (PVD) : vers une approche plus réaliste du problème de la substitution - Siggel, Eckhard (L'Actualité économique, 1982)
AbstractIn this paper it is argued that the conventional estimation of production functions may be misleading for the study of technological progress and technology choice in developing countries. The analysis of technical progress and technology transfers requires empirical production functions which should reflect accurately the state of technology and productivity in a given country or region. The neoclassical production function embracing as an envelope all observations in an industry is likely to overstate the number of techniques already established in the region. It may therefore underestimate the technical progress achieved by further transfers. The problem lies in the very concept of technological progress which is defined as a shift of the universal production function and excludes movements along the production isoquant.As to the choice of technology the estimation of the elasticity of substitution may be equally misleading for the purpose of predicting changes of factor use caused by factor price changes. The substitution possibilites between factors of production in the actually existing choice set of techniques for a given country or region are better described by the concept of a technology shelf. Two important characteristics of the technology shelf are the range and density of substitution. It is argued that industrial engineering information should be used to better describe the technology shelf. In its empirical part, using data of the manufacturing sector of Zaire, the paper shows how such engineering information may be used to estimate the range and density of substitution.